Estimating the elasticity of turnover from bunching: Peferential tax regimes for solo self-employed in Italy - Francesco Alosa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
Turnover is a key indicator of economic activity, but we know little about how much entrepreneurs adjust it as a response to taxation. This is because business taxation is usually based on profits, rather than turnover. This paper exploits the notch created by the eligibility cut-off of the preferential (turnover) tax regime for solo self-employed in Italy to study turnover responses to taxation. I find that solo self-employed bunch below the turnover threshold to be eligible for the preferential scheme. Effects are different in different sectors, with professionals and business intermediaries showing the largest responses. Then, I estimate the turnover tax elasticity by focusing on the (last) marginal buncher. To do so, I adapt the models of Kleven and Waseem (2013) and Harju et al. (2019) to derive a modified indifference condition that fits the institutional set-up. The baseline estimate for the turnover tax elasticity is 0.072.
Keywords: 330; turnover tax elasticity; preferential tax regimes; solo self-employed; bunching